The Relevance of Laduny Science in The Qur’an: Al-Ghazālī’s Perspective on Acquiring Knowledge in Digital Era - Ina Salmah Febriani; Neli Hidayah; Tamimi Setia Alam; Wahyudin Wahyudin (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2023)
Development of technology may influence the way of individual learning. Many years ago, scholars had a long time to acquisition the knowledge, today’s digital era allows us to get information quickly. Imam Al-Ghazālī said that there are three human abilities to obtain knowledge, including the five senses, ‘aql and heart. The heart is one of the media for acquiring laduny knowledge. Al-Quran specifically mentions lafadz ‘ladun’. Lafadz ladun is mentioned 18 times in the Al-Quran with various derivations. The 18 times of lafadz ladun, only on Qs. Al-Kahfi/65 lafadz ladun with ‘ilm (min ladunna ‘ilmaa). This is also the reason why Imam Al-Ghazālī in his book Risalat al-Laduniyyah does not deny that the acquisition of laduny knowledge requires a learning process. This research aims to reinterpret the meaning of ‘laduny’, which has been known as something abstract and difficult to achieve, to become relevant for the millennial generation. The method used in this research is descriptive qualitative. Researchers attempt to analyze various interpretations of classical and contemporary scholars regarding Qs. Al-Kahf/65. From the results of the analysis, it was found that the mufasir Qs. Al-Kahfi/65 regarding the hard efforts of Prophet Musa as to be ‘patient’ to study with Prophet Khidir as. The results of this research are that laduny knowledge is given to whomever Allah wishes as long as with the physical strive (learn) and spiritual strive (tazkiyyat an-nafs) made by the servant.